PENGARUH FINANCIAL LEVERAGE TERHADAP PERATAAN LABA PERUSAHAAN (Studi Pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2017-2020) - Era Yudistira (Akuntansi, 2022)
The company's ability to maintain the existence and sustainability of the company is a demand for management today. With unstable economic conditions and high levels of competition, management must be able to show good and maximum performance to maintain investor confidence. The company's profit that is evenly distributed from year to year is highly favored by management and investors, because even profit indicates that the company is strong and stable. This study uses a quantitative approach with a total sample of 5 companies studied from 2017-2020. From the results of the study it can be concluded that financial leverage does not significantly influence the company's income smoothing. The results of data processing show a significance value of 0.99 or greater than 0.05 and the t count is smaller than the t table which is –1.754 < 2.119. Thus it can be interpreted that H1 which states that there is a significant influence between financial leverage on income smoothing is rejected.